SEJARAH DAN PERKEMBANGAN TRADISI DZIKIR FIDA' DI DESA KINCANG KECAMATAN RAKIT KABUPATEN BANJARNEGARA - Yusuf Iskandar (JSI: Jurnal Sejarah Islam, 2022)
This research is motivated by gratitude and self-approach to Allah SWT in the form of dhikr. The form of this approach is in the form of dhikr fida‟ which is located in Kincang Village, Rakit District, Banjanegara Regency. Dhikr which is rarely done by Muslims, especially NU residents, is still running in Kincang Village. They routinely carry out dhikr fida activities once a week every Friday afternoon. The purpose of this study was to analyze dhikr fida‟ in Kincang Village. Where the analysis is more directed to history and its influence on the people of Kincang Village. This type of research is field research with qualitative methods. With sources obtained through observation, interviews, and documentation. After that the data that has been obtained is then verified, analyzed, and presented the data. And then conclusions are drawn. This study aims to reveal how the history and influence of dhikr fida‟ on the people of Kincang Village. Dhikr fida‟ in Kincang Village was started in 1960 by a community leader from Banyumas. Slowly this dhikr developed and covered the entire Kincang Village. With the dhikr of fida, the people of Kincang Village often hold religious activities. This can be proven by the existence of regular recitations and religious associations.